Difference between revisions of "2001 IMO Problems/Problem 6"

m
Line 15: Line 15:
 
<cmath>(K+L-M+N)(-K+L+M+N)=KM+LN</cmath>
 
<cmath>(K+L-M+N)(-K+L+M+N)=KM+LN</cmath>
 
<cmath>-K^2+KM+L^2+LN+KM-M^2+LN+N^2=KM+LN</cmath>
 
<cmath>-K^2+KM+L^2+LN+KM-M^2+LN+N^2=KM+LN</cmath>
<cmath>L^2+LN+N^2&=&K^2-KM+M^2</cmath>
+
<cmath>L^2+LN+N^2=K^2-KM+M^2</cmath>
 
So, we have:
 
So, we have:
<cmath>(KM+LN)(L^2+LN+N^2)&=&KM(L^2+LN+N^2)+LN(L^2+LN+N^2)</cmath>
+
<cmath>(KM+LN)(L^2+LN+N^2)=KM(L^2+LN+N^2)+LN(L^2+LN+N^2)</cmath>
<cmath>&=&KM(L^2+LN+N^2)+LN(K^2-KM+M^2)</cmath>
+
<cmath>=KM(L^2+LN+N^2)+LN(K^2-KM+M^2)</cmath>
<cmath>&=&KML^2+KMN^2+K^2LN+LM^2N</cmath>
+
<cmath>=KML^2+KMN^2+K^2LN+LM^2N</cmath>
<cmath>&=&(KL+MN)(KN+LM)</cmath>
+
<cmath>=(KL+MN)(KN+LM)</cmath>
 
Thus, it follows that <cmath>(KM+LN) \mid (KL+MN)(KN+LM).</cmath>   
 
Thus, it follows that <cmath>(KM+LN) \mid (KL+MN)(KN+LM).</cmath>   
 
Now, since <math>KL+MN>KM+LN</math> if <math>KL+MN</math> is prime, then there are no common factors between the two.  So, in order to have <cmath>(KM+LN)\mid (KL+MN)(KN+LM),</cmath> we would have to have <cmath>(KM+LN) \mid (KN+LM).</cmath> This is impossible as <math>KM+LN>KN+LM</math>.  Thus, <math>KL+MN</math> must be composite.
 
Now, since <math>KL+MN>KM+LN</math> if <math>KL+MN</math> is prime, then there are no common factors between the two.  So, in order to have <cmath>(KM+LN)\mid (KL+MN)(KN+LM),</cmath> we would have to have <cmath>(KM+LN) \mid (KN+LM).</cmath> This is impossible as <math>KM+LN>KN+LM</math>.  Thus, <math>KL+MN</math> must be composite.

Revision as of 19:09, 4 December 2015

Problem 6

$K > L > M > N$ are positive integers such that $KM + LN = (K + L - M + N)(-K + L + M + N)$. Prove that $KL + MN$ is not prime.

Solution

This problem needs a solution. If you have a solution for it, please help us out by adding it.

First, $(KL+MN)-(KM+LN)=(K-N)(L-M)>0$ as $K>N$ and $L>M$. Thus, $KL+MN>KM+LN$.

Similarly, $(KM+LN)-(KN+LM)=(K-L)(M-N)>0$ since $K>L$ and $M>N$. Thus, $KM+LN>KN+LM$.

Putting the two together, we have \[KL+MN>KM+LN>KN+LM\]

Now, we have: \[(K+L-M+N)(-K+L+M+N)=KM+LN\] \[-K^2+KM+L^2+LN+KM-M^2+LN+N^2=KM+LN\] \[L^2+LN+N^2=K^2-KM+M^2\] So, we have: \[(KM+LN)(L^2+LN+N^2)=KM(L^2+LN+N^2)+LN(L^2+LN+N^2)\] \[=KM(L^2+LN+N^2)+LN(K^2-KM+M^2)\] \[=KML^2+KMN^2+K^2LN+LM^2N\] \[=(KL+MN)(KN+LM)\] Thus, it follows that \[(KM+LN) \mid (KL+MN)(KN+LM).\] Now, since $KL+MN>KM+LN$ if $KL+MN$ is prime, then there are no common factors between the two. So, in order to have \[(KM+LN)\mid (KL+MN)(KN+LM),\] we would have to have \[(KM+LN) \mid (KN+LM).\] This is impossible as $KM+LN>KN+LM$. Thus, $KL+MN$ must be composite.

See also

2001 IMO (Problems) • Resources
Preceded by
Problem 5
1 2 3 4 5 6 Followed by
Problem 6
All IMO Problems and Solutions
Invalid username
Login to AoPS